Reducing turnaround time in a clinical laboratory by using a management model utilizing process automation and lean healthcare - Diaz Amaro, Marcos Antonio (2025)
A clinical Flow Cytometry laboratory underwent a diagnosis of its TAT indicator over a period of one year, finding an excess of 3,83 hours or 15,94% with respect to the 24-hour sector range. The response time (TAT) in a clinical laboratory is an indicator that measures the efficiency and quality of the service offered by delivering results reports on time. A TAT within the established parameters makes it possible to offer rapid treatment to patients, respond to the demand of an aging population and combat limited resources. As a proposal to improve the situation, pilot tests were implemented in the laboratory by applying lean Healthcare tools (KANBAN, SMED) and the automation method to its operational processes. Through a statistical validation of the results obtained through Student's t-test, a reduction of 12,86% of the TAT and the elimination of non-compliant products generated in the laboratory marking area is affirmed. Likewise, the project will be considered economically viable with an IRR of 67% and a B/C of 2.27. Finally, the project also contributes to the sustainable development goals towards 2030 number 3, 8 and 10.